Climate stress and rural livelihoods in Zimbabwe: Unpacking the nexus between agricultural decline and migration - Mugambiwa, Shingirai S (Edelweiss Applied Science and Technology, 2025)
Climate variability is severely threatening rural livelihoods in Zimbabwe, where smallholder farmers rely predominantly on rain-fed crops. Altered precipitation patterns, persistent drought, and episodes of extreme weather have disrupted agricultural schedules, compromised food security, and increased socioeconomic vulnerability. This research assesses the correlation between climate-induced decline in agricultural output and trends in rural–urban and cross-border migration, concentrating on the districts of Mutoko, Gutu, and Chimanimani, which collectively offer a range of agro-ecological environments and significant vulnerability to climatic threats. The study employed a qualitative methodology, utilizing semi-structured interviews and focus group discussions with 36 respondents. The sample included smallholder farmers, female-led households, youth, traditional leaders, and agricultural extension agents. Thematic analysis was utilized to analyze data. The findings indicate that declining harvests, animal mortality, and reduced cropping periods have progressively eroded traditional subsistence, leading to increased out-migration, especially among youth and economically engaged male farmers. The paper recommends the enhancement of agro-ecological resilience via increased smallholder irrigation, the promotion of drought-resistant seed types, and revitalized extension services. Investment in vocational training, along with accessible microfinance and gender-sensitive social protection, can substantially improve adaptive capacity among at-risk groups.